Biodiesel production from Halamphora coffeaeformis microalga oil by supercritical ethanol transesterificati - Patricia I. Leonardi (2019)
The marine benthic diatom Halamphora coffeaeformis is a potential feedstock for biodiesel production. This species shows high growth rates, important triacylglycerol (TAG) contents and grows in seawater making largescale cultivation advantageous. Moreover, sustainable biofuel production in future biorefineries requires the implementation of technologies that employ renewable solvents. Thus, the goal of this work was to evaluate ethanol usage as extraction solvent and reaction medium for biodiesel production from H. coffeaeformis. In a first step a bio-oil extraction was carried out comparing ethanol and n-hexane to investigate the performance of ethanol with respect to a conventional solvent. Then, a free-catalyst supercritical ethanol transesterification of the bio-oils was carried out to obtain biodiesel. Higher lipid extraction yields were obtained using ethanol respect to n-hexane (26 wt.% vs 21.1 wt.%). The transesterification of crude lipids extracted with ethanol as solvent at 305 °C and 40 min. produced up to 15.9 wt.% of biodiesel respect to dried biomass processed. Comparable biodiesel yields were obtained using non-renewable organic solvents and a conventional catalytic technology. Thus, ethanol extraction and subsequent supercritical transesterification of H. coffeaeformis oil proved to be technically feasible and environmental friendly technology for the production of biodiesel.